2015
DOI: 10.1073/pnas.1501844112
|View full text |Cite
|
Sign up to set email alerts
|

Mx1 and Mx2 key antiviral proteins are surprisingly lost in toothed whales

Abstract: Viral outbreaks in dolphins and other Delphinoidea family members warrant investigation into the integrity of the cetacean immune system. The dynamin-like GTPase genes Myxovirus 1 (Mx1) and Mx2 defend mammals against a broad range of viral infections. Loss of Mx1 function in human and mice enhances infectivity by multiple RNA and DNA viruses, including orthomyxoviruses (influenza A), paramyxoviruses (measles), and hepadnaviruses (hepatitis B), whereas loss of Mx2 function leads to decreased resistance to HIV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…1) (Fernandez-Trujillo et al 2013, and references therein). In a recent publication, Braun et al (2015) reported on the discovery of an evolutionary loss of function of Mx for toothed whales, where it was suggested that pseudogenization of Mx hinders the entry of virus particles into host cells, i.e., protecting the ancestral toothed whale species against harmful virus outbreaks (Braun et al 2015). Cumulatively, these findings fit the scenario that lineage-specific gene loss events are adaptive responses towards changes in a species’ environment (Olson 1999).…”
Section: Resultsmentioning
confidence: 99%
“…1) (Fernandez-Trujillo et al 2013, and references therein). In a recent publication, Braun et al (2015) reported on the discovery of an evolutionary loss of function of Mx for toothed whales, where it was suggested that pseudogenization of Mx hinders the entry of virus particles into host cells, i.e., protecting the ancestral toothed whale species against harmful virus outbreaks (Braun et al 2015). Cumulatively, these findings fit the scenario that lineage-specific gene loss events are adaptive responses towards changes in a species’ environment (Olson 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple functional losses have occurred across evolution for MxB (MX2), either by pseudogenization or via gene coversion from MxA genes. Notably, both MX genes are nonfunctional in Odontoceti cetaceans (toothed whales, including dolphins and orcas) and this loss occurred soon after the divergence of Odontocetes and Mystocetes (baleen whales) ~33–37 Mya (222). Presumably compensation occurs elsewhere in the genome since examination of 56 other mammalian genomes have found both MX genes to be intact.…”
Section: Specialized Adaptations Of Mammalian Macrophages: Comparisonmentioning
confidence: 99%
“…(acute inflammatory response)、细胞防御反应(cellular defense response)以及细菌防御反应(defense response to bacterium)相关 [11] , 暗示了基因的丢失可能是鲸类 免疫适应的驱动力之一; 与病毒感染防御相关基因 (Mx1, Mx2)在齿鲸中的丢失进一步支持该结论 [115] .…”
Section: 的基因家族出现基因收缩 多数与急性炎症反应unclassified